Effects of aquatic exercises on physical fitness and quality of life in postmenopausal women: an updated systematic review and meta-analysis - Zhou, Wen-Sheng; Mao, Su-Jie; Zhang, Shi-Kun; Xu, Hong; Li, Wei-Lu (Frontiers in Public Health, 2023)
Objective In the present systematic review and meta-analysis, we aimed to evaluate and update the effects of aquatic exercise on physical fitness and quality of life (QoL) in postmenopausal women. Methods The databases Cochrane Library, PubMed, Web of Science, and MEDLINE were searched for randomized controlled trials (RCTs) on the topic from inception to July 2022. The GetData software was used to extract data from the published images. RevMan5.4 software was used for statistical analysis. Data are expressed as standardized mean difference (SMD) with 95% confidence intervals (CI). I2 index was employed for heterogeneity. Egger's test was used to assess publication bias. We evaluated the methodological quality of included studies using the Physiotherapy Evidence Database scale. Results We included 594 participants in 16 RCTs (19 comparison groups). The results indicated that aquatic exercise can significantly improve lower limb strength (LLS), upper limb strength (ULS), agility, flexibility, and overall QoL. No significant effects were found on aerobic capacity. Subgroup-analysis results indicated that aquatic exercise only significantly improved LLS, ULS, agility, and flexibility in postmenopausal women < 65 years of age. However, aquatic exercise improves the overall QoL both in postmenopausal women < 65 years and ≥ 65 years. Aquatic resistance exercise significantly improves LLS, ULS, agility and flexibility. In addition, aquatic aerobic exercise can effectively increase LLS, and combined aquatic aerobic and resistance exercise can enhance the overall QoL. Conclusions Aquatic exercise can effectively improve physical fitness and overall QoL in postmenopausal women, but has limited effects on aerobic capacity; thus, it is highly recommended in postmenopausal women.